Doctor Oviedo Pérez Pérez - Denia Morales Navarro (Editorial Ciencias Médicas, 2013)
On the night of Tuesday, July 16, 2013, we received the painful news of the sudden death of the Doctor in Stomatological Sciences Oviedo Pérez Pérez, a specialist in the II degree in Maxillofacial Surgery and a master's degree in stomatological emergencies. At the time of his death he held the main teaching category of assistant professor and held the position of Vice Dean of Research and Postgraduate of the Faculty of Stomatology of the University of Medical Sciences of Havana. Oviedo was born on February 2, 1962 in Holguín and entered the Faculty of Stomatology of the Higher Institute of Medical Sciences of Santiago de Cuba in 1984, graduating as Doctor in Stomatology in 1984. In 1992 he began the specialty of Maxillofacial Surgery at Saturnino Hospital Lora, from Santiago de Cuba, which ended in 1995. From early moments he joined the undergraduate teaching of the career of Stomatology, transiting through the different teaching categories to reach the Auxiliary Teacher in 2008. He was an active member in the preparation of new educational technologies of the subject of surgery oral. He co-authored several monographs that have served as complementary teaching material for pre and postgraduate teaching. Since 2004 he worked at the Faculty of Stomatology of Havana, moving to occupy in 2005 the position of Head of Postgraduate Department. In 2007, he was promoted to Vice-Dean of Postgraduate Studies and in 2010, due to changes in the structure of the position, the Vice-Dean of Postgraduate Studies was merged with the Vice-Dean of Research, also assuming this post. He was the author of 37 national and international publications. He presented 50 scientific papers in international events and 74 in national ones. He received 58 postgraduate courses and taught 55. He was part of the Cuban Society of Maxillofacial Surgery and the Latin American Oral Implantology Society (SIOLA). He received several scientific acknowledgments throughout his career, including the one of the College of Graduated Dentist Surgeons of the UABC, Mexicali, Baja California, Mexico, in 2009; and that of the Spanish Society of Implants and Gerodontology in 2010 and 2011, respectively. He was part of numerous courts for the passing of the year and completion of the specialty of Maxillofacial Surgery and masters. Collaborated with the Infomed Maxillofacial Surgery site. He was part of the Rector's Advisory Board for specialties. He recently received the title of Doctor in Stomatological Sciences, as a culmination to his investigative work in the field of oral Implantology. Oviedo Pérez Pérez was a worthy example for our profession. He excelled in assistance, teaching, research and in management. The Cuban Stomatology is dressed in mourning for its early physical loss.